Stealth missiles with precision guidance: A novel multifunctional nano-drug delivery system based on biomimetic cell membrane coating technology - Yuyan Zhou; Xinyue Wang; Xiaorong Tian; Deyu Zhang; Hanxiao Cui; Wei Du; Zhenghui Yang; Jiayu Li; Wanshun Li; Jiaheng Xu; Ying Duanmu; Ting Yu; et al. (Materials Today Bio)
Nanodrug delivery systems (NDDSs) have demonstrated broad application prospects in disease treatment, prevention, and diagnosis due to their nanoscale size advantages and high drug-loading capacity. However, their clinical translation still faces multiple challenges, including rapid clearance by the reticuloendothelial system (RES), nonspecific targeting, and insufficient efficiency in crossing biological barriers. Cell membrane-coated biomimetic delivery systems (CMC-BDS), which integrates natural cell membranes onto nanoparticle (NPs) surfaces, provides nanodrugs with a versatile ''biomimetic cloak,'' representing a highly promising surface engineering strategy. This approach enables nanocarriers to inherit the intrinsic biological properties of different cell sources, endowing them with immune evasion, prolonged circulation, dynamic targeting, biocompatibility, and biodegradability, while supporting the integration of diverse biomedical functions. Furthermore, surface functionalization modifications can enhance their programmability, multifunctionality, and biointerface adaptability, thereby optimizing targeted delivery efficiency and extending in vivo circulation time. This review first outlines the development and key preparation steps of cell membrane coating technology. It then discusses the selection strategies for various cell membrane types—including leukocyte, erythrocyte, platelet, dendritic cell, tumor cell, and bacterial membranes—while comparing their respective advantages and limitations. Finally, the review highlights recent advances in applying cell membrane-coated nanoparticles (CMC-NPs) for treating tumors, ischemic stroke, and inflammatory diseases.